Relationship Between Learning Assistance with Children's Learning Outcome During The COVID-19 Pandemic at Junior High Shool 7 Sijunjung Regency - Triwindi Novitri; Wisroni Wisroni (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research was motivated by the low learning outcomes of children during the COVID-19 pandemic at SMPN 7 Sijunjung. Due to alleged learning support during the COVID-19 pandemic's learning process.The goals of this study are to look at the description of learning assistance at SMPN 7 Sijunjung during the Covid-19 pandemic, the learning outcomes of children at SMPN 7 Sijunjung during the pandemic, and the relationship between learning mentoring and children's learning outcomes during the pandemic.SMPN 7 Sijunjung hosts covid-19.This is a quantitative study with a correlational methodology.The participants in this study were 161 students in class VIII at SMPN 7 Sijunjung, who were separated into five classes. This study's sample was drawn from 50% of the population, or 80 people, using cluster random sampling.A questionnaire was utilized for data collecting, and the percentage formula and the product moment formula were used for data analysis.The findings of this study show that (1) children's learning assistance during the covid-19 pandemic at SMPN 7 Sijunjung is not good, (2) children's learning outcomes during the covid-19 pandemic at SMPN 7 Sijunjung are still low, and (3) there is a link between learning assistance and learning outcomes during the covid-19 pandemic at SMPN 7 Sijunjung.During the COVID-19 pandemic, there was a substantial difference in learning support and children's learning outcomes at SMPN 7 Sijunjung